PENGARUH KOMUNIKASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI UNIVERSITAS SELAMAT SRI (UNISS) KENDAL - Lailatul Wulansari (Jurnal Ekonomika dan Bisnis, 2019)
This study aims to determine whether communication and work motivation have a significant influence on employee performance at Selamat Sri University (UNISS) Kendal. The population and sample in this study were 60 Selamat Sri University (UNISS) Kendal employees. Data analysis in this study uses validity, reliability, classical assumption test, multiple regression analysis, hypothesis testing, and test coefficient of determination.The results showed that communication and motivation had a positive and significant effect on the performance of employees at Selamat Sri University (UNISS) Kendal both influential partially and simultaneously. From the results of the determination coefficient test shows that the communication and motivation variables have a contribution in influencing employee performance variables by 29.1%